Disruption, Change and Transformation in Organisations A Human Relations Perspective - Day, Andrew (Routledge, 2020)
This book explores the psychological and social dynamics of continuous, disruptive and discontinuous change. It examines the emotional strain and challenges of disruption, studies the nature of organisational transformation and examines what can be done to develop an organisation's capacity to adapt and thrive in turbulent environments. An organisation's long-term survival increasingly rests on its adaptive capacity, ability to continuously change and transform itself. Yet, people experience ongoing and fundamental change to be disorientating and unsettling as it challenges accepted assumptions and identities. This book assists leaders and change practitioners understand these dynamics, help people to make sense of change and to create the conditions that enable people to self-organise and creatively adapt. With case studies and personal accounts from individuals and companies, this is an ideal resource for practitioners and managers dealing with organisational change, as well as students, academics and researchers
Description based upon print version of record. - Implications for practice
Keywords: Organizational change; Psychology, Industrial; Organisationswandel; Human relations; Dynamik